Sexual Violence as a Predictor of Unwanted Pregnancy: Evidence from the 2013 Nigeria Demographic and Health Survey - A., Titilayo; O.O., Ekundayo; O.J., Olaoye-Oyesola; A.O., Anuodo (European Scientific Journal, ESJ, 2017)
Gender-based domestic violence (GBDV) continues to pose a serious threat to woman folk and the society at large. All efforts to reduce the menace have not yielded an impressive result and thus, the prevalence rate is still unacceptably high. Employing analytic nationally representative weighted sample size, 15,941women aged 15-49 years who were currently pregnant or ever had at least one pregnancy experience were interviewed for domestic violence through quantitative instrument (questionnaire). The data were analysed with a chi-squared test and binary logistic regression using STATA 13. Overall, one quarter (24.7%) of the total respondents who ever experienced domestic violence from their spouses or intimate sexual partners reported having experienced unwanted/unintended pregnancy. It was evident in the study that GBDV is significantly related to unwanted pregnancy even after controlling for all other tested independent variables like age, educational attainment, wealth index, religion, place of residence and other fertility related variables such as number of children ever born, contraceptive use and pregnancy termination experience. Spousal abuse in any form is a crucial predictor of unwanted pregnancy in Nigeria. Therefore, addressing gender-based domestic violence is critical to reducing the menace of unwanted pregnancy and taming unnecessary population growth in Nigeria.